Tropes of fear and the crisis of the west: Trumpism as a discourse of post-territorial coloniality*. Issue 2 (3rd April 2017) - Çalışkan, Gül; Preston, Kayla
ABSTRACT: We examine 'Trumpism' as a contemporary form of colonial domination, showing how this discourse represents both a crisis of coloniality and a stimulus for a movement of 'decoloniality'. A critical discourse analysis is applied to seven speeches delivered by Donald Trump between his announcement of his presidential candidacy in June 2015 and his inauguration in January 2017. In assessing Trump's arguments, we focus mainly on those concerning national security, illegal immigration, and the threats posed by various foreign countries. Although these arguments sit within a long colonial tradition, they also indicate a crisis of modernity, as witnessed in the growing challenges to colonial masculinity, nationalism, and rationality. We conclude that Trumpism articulates a reaction to these challenges, and that Trump's rise to power is a symptom of the crisis of post-territorial coloniality in contemporary global society.